1991
DOI: 10.1111/j.1365-2494.1991.tb02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbage production and quality of a range of secondary grass species at five rates of fertilizer nitrogen application

Abstract: The productivity of ten grasses was measured under six cuts per annum for 3 years and three cuts for a fourth harvest year in comparison with a perennial ryegrass (Lolium perenne) control. The grasses were Yorkshire fog (Holcus lanatus), two red fescues (Festuca rubra), creeping bent (Agrostis stolonifera), bent (Agrostis castellana), bent (Agrostis capillaris), smooth meadow‐grass (Poa pratensis), crested dogstail (Cynosurus cristatus), sweet vernal (Anthoxanthum odoratum) and timothy (Phleum bertolonii). Ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 18 publications
9
55
2
1
Order By: Relevance
“…Common bent occurs widely in grassland on impoverished soils and can be an indicator of low P conditions (Peeters 2004). Yorkshire fog is capable of growing under low soil fertility (Watt 1978) and has a higher DM production potential at low N than perennial ryegrass (Frame 1991). In contrast, rough stalked meadowgrass, a major component of the meadow grass fraction, is associated with grassland on fertile soils (Peeters 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common bent occurs widely in grassland on impoverished soils and can be an indicator of low P conditions (Peeters 2004). Yorkshire fog is capable of growing under low soil fertility (Watt 1978) and has a higher DM production potential at low N than perennial ryegrass (Frame 1991). In contrast, rough stalked meadowgrass, a major component of the meadow grass fraction, is associated with grassland on fertile soils (Peeters 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Frame (1991) has shown that the highest yielding of the so-called secondary grasses (those not usually sown but ingressing with sward age) can outyield perennial ryegrass at low fertilizer application rates (up to 200 kg N ha −1 ). The data from this study also support the conclusion drawn by Collins and Murphy (1979) from their survey data of grassland in Ireland that soil fertility is more important than botanical composition in determining the productivity of grassland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar changes in botanical composition have been observed with cessation of fertilizer application, with species indicating nutrient-rich conditions such as L. perenne being replaced by species indicating nutrient-poorer conditions (Dahmen, Kuhbauch & Thome, 1989;Oomes, 1990;OlflF & Bakker, 1991). The invading ' secondary' grass species are often more suited than L. perenne to adverse conditions such as reduced N levels (Frame, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Creeping bent (Agrostis stolonifera) is one of the most important and productive secondary grasses in British agriculture (Haggar, 1976 ;Frame, 1991). This species is a dominant component of old permanent pasture (Bailey, 1997), and under conditions of sub-optimal nitrogen (N) supply ( 160 kg fertilizer N ha −" yr −" ) is also a vigorous colonizer of perennial ryegrass reseeds (Whinham & Beaverstock, 1985 ;Stevens & Laughlin, 1996).…”
Section: mentioning
confidence: 99%